Integration of Six Sigma and Fuzzy Fmea to Reduce Oil Losses in The Crude Palm Oil (CPO) Processing Industry in Central Kalimantan - Afriani, Dian Lusi; Suparno, Suparno (Ridwan Institute, 2025)
Oil loss during Crude Palm Oil (CPO) processing poses a significant challenge for palm oil mills, leading to decreased productivity, economic losses, and reduced sustainability. This study aims to identify and reduce the causes of oil losses at PT. XYZ in Central Kalimantan using an integrated approach of Six Sigma and Fuzzy Failure Mode and Effect Analysis (FMEA). The research was conducted by analyzing production data from June to August 2024, focusing on oil losses in press cake fiber, empty bunches, and final effluent. The Six Sigma DMAIC method was applied to define, measure, analyze, improve, and control critical factors in the process. The Fuzzy FMEA was used to prioritize potential failures and reduce subjectivity in risk assessment. Results show that final effluent contributed the highest oil loss (37%), followed by press cake fiber and empty bunches. The overall process achieved a sigma level of 4.11, indicating potential for further improvement. Key causes included inconsistent separation processes and inadequate operator monitoring. Suggested improvements involve automation, SOP enforcement, and visual aids through poka-yoke mechanisms. This research provides valuable insights for quality improvement and operational efficiency in the palm oil industry and can be adopted by similar processing plants seeking to reduce losses and increase competitiveness.